Welfarism and extra-welfarism: a critical overview - Brayan Viegas Seixas (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2017)
Abstract: Rules and principles for guiding decision-making in the health care sector have been debated for decades. Here, we present a critical appraisal of the two most important paradigms in this respect: welfarism and extra-welfarism. While the former deals with the maximization of the overall sum of individual utilities as its primary outcome, the latter has been focusing on the maximization of the overall health status. We argue that welfarism has three main problems: (1) its central idea of overall sum of individual utilities does not capture societal values decisively relevant in the context of health; (2) the use of the Potential Pareto Improvement brings an unresolvable separation between efficiency and equity; and (3) individual utility may not be a good measure in the health sector, given that individuals might value things that diminish their overall health. In turn, the extra-welfarist approach is criticized regarding four main limitations: (1) the advocated expansion of the evaluative space, moving from utility to health, may have represented in reality a narrowing of it; (2) it operates using non-explicit considerations of equity; (3) it still holds the issue of "inability to desire" of unprivileged people being considered the best judges of weighing the criteria used to building the health measures; and (4) there is controversial empirical evidence about society members' values that support its assumptions. Overall, both paradigms show significant weaknesses, but the debate has still been within the realm of welfare economics, and even the new approaches to resource allocation in health care systems appear to be unable to escape from these boundaries.